The Analysis Of Risk Management Of Projects With Lumpsum Contract System and Unit Price Contract System Using AHP Method (Case Study Of Contractors In Semarang City) - Muhammad Taufik; Kartono Wibowo; Abdul Rochim (International Conference on Coastal and Delta Areas, 2017)
In the construction project implementation, the contract is a bond between the project owner as the service user and the implementer / contractor as the service provider. The contract outlines the forms of cooperation, whether technical, commercial, or legal in a clear and detailed way. A fair contract should balance the rights and obligations between the two parties. So both parties should look at the articles in the contract so that the things that pose risks can be avoided. In the project implementation, the usual contracts are Lumpsum contract and Unit Price contract. The method used is Analytic Hierarchy Process (AHP) Method. The analysis process begins by defining the problem, and creating a hierarchical structure. This hierarchy consists of 3 (three) levels of objectives (level I), criteria (level II), and alternative (level III). Based on the hierarchy and then compiled questionnaires, Questionnaires were distributed to 71 respondents consisting of contractors in Semarang. The data obtained are then tabulated, followed by pairing matrices, pairing comparisons, measuring priority weights for level II and level III, and checking for consistency. This means that projects with lumpsum contracts are at higher risk of losses compared to unit price contracts. The Based on the result of cost swelling risk analysis, we get the priority weight for lumpsum contract equal to ≥50% and contract unit price ≤50%. Keywords: Risk, Methank, Analytic Hierarchy Process (AHP).